The Hesitation of Anxious Traders in an Agent-Based Model. (14th October 2022) - Tang, Bao-Jun; Lin, Kun-Ben; Huang, Jing-Bo; Lin, Hung-Wen
Abstract : Anxiety prevails in financial markets. In accordance with psychological research, anxious traders' hesitant behavior differs from the frequently dissected herding and speculative behaviors. This paper examines the interactions between agent anxiety and price inertia in an artificial financial market. We incorporate an evolutionary mechanism to analyze the strategic benefit of the boundedly rational anxious agent. According to our simulation results, deviations in asset prices from their fundamentals increase with the behavioral hesitation of the anxious agent. The investment rigidity from the anxious agent's lack of confidence mitigates the possibility of price reversal. Moreover, the average strategic benefit of the anxious agent is close to zero. To ensure the reliability of our finding, we further include the irrationality of the anxious agent in our evolutionary setting. Such an endeavor again demonstrates that the strategic benefit of the fundamentalist agent is inferior to that of the anxious agent. Since the anxious agent is characterized by an intolerance for uncertainty, we also investigate the artificial market under various degrees of risk aversion. We perceive that it is less possible for price reversal to emerge when considering higher levels of hesitation. The behavioral hesitation of the anxious agent enables the agent to cleverly evade the risk raised by the speculator.